Revisiting Art Deco in the UK - Massey, Anne (The Routledge Companion to Art Deco, 2019)
This chapter begins with a look back at the historiography of Art Deco in the UK, starting from the first book to appear on the subject in 1968. It utilizes the theme of historiography and the passing of time to explore the work of interior designer, Oliver Percy Barnard and his refit of the basement of the Regent Palace Hotel, which has been meticulously restored to its Art Deco splendor. The chapter investigates the design histories published in books and the interiors, which have existed in various forms over a number of years, are part of an overall network of objects and of the people of Art Deco. An exploration of the case study allows for a leveraging of the contemporary into a consideration of the past, just as the re-reading of Hollywood Beyond the Screen has triggered the preceding brief review of the historiography of Art Deco in the UK.